Building inclusive excellence in STEM: a 15-year analysis and Lessons Learned of the Alfred P. Sloan Foundation Minority Ph.D. Program at the University of South Florida - Diaz-Elsayed, Nancy; Acuna, Jorge A.; Henderson, Michelle; Isaacs, Wainella; Cantarino, Daniela; Bosson, Jennifer K.; Polk, Tramaine; Robinson, Patricia; Batson, Bernard; Zayas-Castro, José L. (Frontiers in Education, 2023)
In 2016, only 7 percent of African American and Hispanic students earned research doctorates in the critical disciplines of engineering, computing, and the physical sciences. In academia, diversity fairs even worse as historically underrepresented minorities represented just 6.1 percent of tenured and tenure-track faculty in engineering. The aim of this effort is to understand the "best practices" for the recruitment and mentoring of minority doctoral students in science and engineering disciplines. This was achieved through a literature review, surveys and focus groups with members of the University of South Florida's (USF's) Sloan University Center of Exemplary Mentoring (UCEM), and interviews with faculty champions. Between 2005 and 2020, 136 graduate students have been supported (43% African American, 56.2% Hispanic, 0.8% Native American), of which 87 percent are expected to earn doctorate degrees. Results indicate that the decision to apply and enroll at USF was largely driven by the alignment of research interests with potential advisors, the quality of funding, and positive interactions with mentors, enrolled students, and alumni who provide evidence of a welcoming climate. Ten practices for mentoring doctoral students are provided, which include creating and promoting an inclusive environment and providing a student-centered approach to mentoring. Our effort to build inclusive excellence and foster social justice in graduate education for African American and Hispanic doctoral students in science, technology, engineering, and mathematics (STEM) is one that can be modeled and adapted by other institutions to align with their institutional culture and values.